Binary Phase Shift Keying Demodulation & its Simulation on MATLAB (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper describes about BPSK demodulation using costas loop and implementing on a DSP kit. Carrier recovery is done using a costas loop which requires a PLL. PLL contains a phase detector, VCO and a LPF which are simulated in MATLAB. Costas loop contains two PLLs which are in quadrature with each other. The BPSK modulation by representing binary data by different phases of a sinusoidal signal and demodulation by using Costas loop is implemented on MATLAB. The MATLAB codes are written to plot the various graphs for input, error voltage and VCO frequency and the demodulated output for the digital binary data taken from the user.